2007
DOI: 10.1021/mp070028i
|View full text |Cite
|
Sign up to set email alerts
|

Biopharmaceutics Classification of Selected β-Blockers:  Solubility and Permeability Class Membership

Abstract: The purpose of this study was to determine the permeability and solubility of seven beta-blockers (acebutolol, atenolol, labetalol, metoprolol, nadolol, sotalol, and timolol) and to classify them according to the Biopharmaceutics Classification System (BCS). Apparent permeability coefficients (Papp) were measured using the Caco-2 cell line, and the solubility was determined at 37 degrees C over a pH range of 1.0-7.5. The permeability coefficients ranged from 1.0x10(-7) to 4.8x10(-5) cm/s. On the basis of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
85
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 28 publications
8
85
1
1
Order By: Relevance
“…In addition, nadolol, a low passive permeability benchmark, was also used to confirm the integrity of the monolayers of Caco-2 cells. The permeability values of nadolol were within the acceptable range of the in-house data (on file at Incyte Corporation) and were also consistent with the values reported in the literature (Yang et al, 2007). All transport experiments were conducted between 22 and 25 days after seeding.…”
Section: [ 3 H]thiamine and [supporting
confidence: 83%
“…In addition, nadolol, a low passive permeability benchmark, was also used to confirm the integrity of the monolayers of Caco-2 cells. The permeability values of nadolol were within the acceptable range of the in-house data (on file at Incyte Corporation) and were also consistent with the values reported in the literature (Yang et al, 2007). All transport experiments were conducted between 22 and 25 days after seeding.…”
Section: [ 3 H]thiamine and [supporting
confidence: 83%
“…Pregabalin is an example of a hydrophilic compound whose high extent of absorption was long believed to result from paracellular diffusion until a highly expressed amino acid transporter was implicated in its intestinal transport (53). Similarly, we believe that the high extent of absorption and low Caco-2 permeability of sotalol likely involves a highly expressed intestinal transporter in contrast to some authors who hypothesize that sotalol's high extent of absorption is due to paracellular diffusion (12,41,74). For these Case 3 drugs, Caco-2 will not be able to predict the high intestinal absorption of these hydrophilic compounds due to the cellular membrane's significant underexpression of relevant transporters compared to the human intestine.…”
Section: Differences In the Paracellular Junctions Between Caco-2 Andmentioning
confidence: 70%
“…Yee (10) had reported that Caco-2 can accurately predict the human intestinal permeability or absorption of compounds regardless of transcellular, paracellular, and carrier-mediated transport mechanisms. However, there are Caco-2 permeability results that disagree with measured human intestinal permeability rates or measured extents of human intestinal absorption (11,12).…”
Section: Introductionmentioning
confidence: 91%
“…9,10) These differences are considered to be attributed to the presence of an unstirred water layer (UWL) on the surface of epithelial cells. [11][12][13] A UWL is a considerable permeability barrier that greatly affects in vitro, but not in vivo, drug absorption experiments.…”
mentioning
confidence: 99%